ANALYSIS OF THE NEEDS OF TEACHING MATERIALS ON SOUND AND TYPES OF MUSICAL INSTRUMENTS FOR GRADE 4 ELEMENTARY SCHOOLS - Mahardika, Putri; Respati, Resa; Ganda, Nana (Program Studi PGMI, 2024)
His study concerns the analysis of the needs of teaching materials on sound material and types of musical instruments. The purpose of this research was to determine the need for teaching materials on sound material and types of musical instruments. The approach used is by using a qualitative approach. Data obtained by observation techniques, interviews, and documentation studies. Based on the implementation of observations, interviews, and documentation studies, it was found that the need for teaching materials on sound material and types of musical instru-ments can be in the form of electronic modules. The electronic modules needed are in accord-ance with the development of grade IV elementary school children, namely they must have an attractive appearance, choose a striking color, use the appropriate type of writing, use simple language, and practice questions in the form of a game. This research has the benefit that it can be used as a reference or basis in developing teaching materials in the form of electronic modules. So that the teaching materials used in learning can meet the needs of students.